Market-Based Redispatch in Zonal Electricity Markets: The Preconditions for and Consequence of Inc-Dec Gaming - Lion Hirth; Ingmar Schlecht (ZBW – Leibniz Information Centre for Economics, 2020)
In zonal electricity markets such as Europe's, system operators rely on out-of-the-market measures to relieve network congestion within bidding zones. One such measure is “redispatching” power plants, i.e. increasing the output of a station downstream of the congestion while lowering production of an upstream plant. Traditionally, generators have often been legally obliged to participate in redispatch and were subsequently compensated for costs incurred. In recent years numerous proposals have been made to organize redispatch through voluntary markets, including one by the European Commission. In this paper, we introduce a simple graphical game-theoretical model of a locational redispatch market within a one-zone electricity market. We solve the model explicitly by determining optimal bidding strategies and the Nash equilibrium. We show that market parties anticipate the redispatch market and bid strategically in the zonal market – this is the so-called increase-decrease game. As a result, grid congestion is aggravated, producers extract windfall profits, financial markets are distorted, and perverse investment incentives emerge. Despite claims to the contrary, we show that such gaming is possible absent any market power, i.e. under perfect competition. At the root of the problem is an inconsistent setup of power markets: combining a zonal with a locational market yields undue arbitrage oppor-tunities that rational firms exploit. We conclude that such inconsistent market design should be avoided.
Keywords: 330